Testing Vision Picking Technology in Warehouse Operations: Evidence From Laboratory Experiments - Gialos, Anastasios; Zeimpekis, Vasileios (International Journal of Industrial Engineering and Management, 2020)
Lately, the complexity of warehouse operations has increased significantly due to the increase of same-day deliveries, customer requests for frequent and low-volume orders as well as the need for faster response times. Although all warehouse processes are critical, order picking contributes significantly to the total operational warehouse costs and affects also customer service level. The aim of this paper is to present evidence from laboratory experiments that evaluate vision picking technology in both accuracy and time efficiency lev- el. We adopt the Design of Experiments (DoE) methodologyin order to examine the impact of four parameters that affect the performance of the system. The results are encouraging showing the benefits that order pickers may have by adopting the proposed technology. Article history: Received (August 31, 2019); Revised (January 6, 2020); Accepted (january 8, 2020); Published online (February 3, 2020)